2013
DOI: 10.1177/0022219413507604
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety Among College Students With Specific Reading Disability (Dyslexia)

Abstract: Test anxiety and its correlates were examined with college students with and without specific reading disability (RD; n = 50 in each group). Results indicated that college students with RD reported higher test anxiety than did those without RD, and the magnitude of these differences was in the medium range on two test anxiety scales. Relative to college students without RD, up to 5 times as many college students with RD reported clinically significant test anxiety. College students with RD reported significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 58 publications
(65 reference statements)
3
34
0
5
Order By: Relevance
“…Over the last decade or so, clinicians, teachers, and researchers have become increasingly concerned that people with poor reading are at increased risk for poor emotional health. This concern is supported by studies reporting statistically significant associations between poor reading and emotional problems (e.g., Boyes et al, 2016;Carroll & Iles, 2006;Francis et al, 2019;Nelson, Lindstrom & Foels, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Over the last decade or so, clinicians, teachers, and researchers have become increasingly concerned that people with poor reading are at increased risk for poor emotional health. This concern is supported by studies reporting statistically significant associations between poor reading and emotional problems (e.g., Boyes et al, 2016;Carroll & Iles, 2006;Francis et al, 2019;Nelson, Lindstrom & Foels, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…The findings were differently significant among the comparison groups. In all working memory measures, students without dyslexia scored significantly higher compared to students with dyslexia (Ghani & Gathercole, 2013;Nelson, Lindstrom, & Foels, 2015). For the study skills results, older students with dyslexia scored lower on anxiety, concentration, and attention, selecting main ideas, time management, and test strategies (Ghani & Gathercole, 2013).…”
Section: The Association Of Dyslexia and Weak Working Memorymentioning
confidence: 95%
“…In a study conducted by Nelson, Lindstrom and Foels (2015), they found that those with higher general intelligence, nonverbal skills and working memory had lower levels of test anxiety. Individuals with learning disabilities and those with behaviour disorders demonstrate elevated levels of test anxiety (Bryan, Sonnefeld & Grabowski, 1983;Dan & Raz, 2015;Nelson et al, 2015), as do adolescents with intellectual disabilities (Poulomee, 2013).…”
Section: Risk Factorsmentioning
confidence: 98%